Estimating the Carbon Footprint of Civil Electrical Diesel Generators in Baghdad City - Alaa Abed; Basim Wahab; Aqeel Salman (Iraqi Geological Journal)
The research objective is to guess the carbon footprint value generated by civil electrical diesel generators (EDGs) in terms of carbon dioxide. This research evaluates the carbon footprint of electrical diesel generators in Baghdad throughout 2023. In this work, carbon footprint refers to the total CO2 generated by all EDGs. The total carbon footprint (CO2 generated) is 3454235.9 tons/year. The Al-Rusafa side has a larger number of EDGs than the Al-Karkh side. As a result, Al-Rusafa generates more electricity and CO2, producing 2,980.95 GWh/year and emitting 2,086,665.8 tons/year of CO2, compared to Al-Karkh, which generates 1,953.67 GWh/year and emits 1,367,570.1 tons/year of CO2. This is due to the larger population on the Al-Rusafa side compared to the Al-Karkh side. First Al-Sadr City and the Second Al-Sadr City sectors have the highest effective carbon footprint (effective CO2 generated) values, at 12460.19 tons/year km2 and 13214.79 tons/year km2, respectively. While the lowest value for the effective carbon footprint in Al-Dora is 4011.236 tons/year km2.